GM Dawson and the Glaciation of Western Canada - Brookes, Ian (Geoscience Canada, 2002)
Summary This paper examines the contributions of G.M. Dawson (1849-1901) to our understanding of the glaciation of the Interior Plains and Cordillera of Western Canada. Dawson is highly esteemed in the history of Canadian geology for his extensive explorations beginning in 1873, which contributed greatly to our knowledge of geography and the geology of Western Canada. The distances travelled and the areas described by Dawson were truly astonishing - hard to comprehend as the accomplishment of a man who was stunted in growth and deformed in stature by a childhood spinal disease,which was indirectly responsible for his early death. Dawson is most widely recognized for his conception of a "Cordilleran glacier" over BritishColumbia, which has proved correct, and continues to be refined rather than revised. This should have placed him squarely within the group of later nineteenth century Canadian geologists who switched their allegiance from the Drift Theory to the Glacier Theory, or who matured wholly with the latter.However, from this first detailed examination of Dawson's works on glaciation, it emerges that, except for the "Cordilleran glacier" hypothesis, in amajority of cases he argued not even the most obvious objections or the plainest of alternatives to his 'Drift' explanations, although he cannot have been unaware of them. No explanation of this rigidity readily presents itself, other thanpossible filial respect for the reputation of his scientifically conservative father,J.W Dawson. Dawson's later contemporaries, including Bell, Low and Tyrrell, ignored rather than challenged his interpretations, developing 'Glacial' theory along paths it has followed to the present day.